2012
DOI: 10.1088/0957-4484/23/39/395604
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous Ge electrode as a template for nano-sized ( < 5 nm) Au aggregates

Abstract: In this paper we present the extremely peculiar electrical properties of nanoporous Ge. A full and accurate electrical characterization showed an unexpected and extremely high concentration of positive carriers. Electrochemical analyses showed that nanoporous Ge has improved charge transfer properties with respect to bulk Ge. The electrode behavior, together with the large surface-to-volume ratio, make nanoporous Ge an efficient nanostructured template for the realization of other porous materials by electrode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 53 publications
(73 reference statements)
0
17
0
Order By: Relevance
“…Recent work by Impellizzeri et al 60 studied the electrical properties of nanostructured Ge and revealed that the nanostructured morphology has unusually high electrical conductivity as compared with the crystalline and nonporous amorphous counterparts. In conjunction with the very large surface area to volume ratio, this makes the nanostructured morphology attractive for a variety of applications.…”
Section: Applications Of the Nanostructured Morphologymentioning
confidence: 99%
“…Recent work by Impellizzeri et al 60 studied the electrical properties of nanostructured Ge and revealed that the nanostructured morphology has unusually high electrical conductivity as compared with the crystalline and nonporous amorphous counterparts. In conjunction with the very large surface area to volume ratio, this makes the nanostructured morphology attractive for a variety of applications.…”
Section: Applications Of the Nanostructured Morphologymentioning
confidence: 99%
“…In addition, previous studies demonstrate that these porous Ge show enhanced conductivity and excellent transport properties 13 .…”
Section: Discussionmentioning
confidence: 96%
“…The thin film sample geometry and the deposition conditions are summarized in in fig.1. The formation of nanostructured porous Ge was reported to occur during implantation of Ge at room temperature (RT) with several heavy ions 12,13,14 . The resulting in-depth damage distribution consists of a porous amorphized Ge layer lying on a continuous amorphous layer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These structures found prospective applications in anodes for electric batteries [1], solar cells [2], filters [3] and gas sensors [4]. Energetic ion irradiationinduced structural modifications such as nanohole patterns [5] or nanoporous, sponge-like structures formation in germanium [6,7] over a range of energies varying from few keV [8][9][10] to several MeV [7,11] have been studied by several groups. Steinbach et al [6] reported porous Ge formation during low-energy heavy ion irradiation of crystalline Ge (c-Ge) at room temperature.…”
Section: Introductionmentioning
confidence: 99%